A comprehensive bioinformatics analysis of fatty acid metabolism-associated genes in the diagnosis and prognosis of head and neck squamous cell carcinoma - Shirin Alsadat Hashemi Fesharaki; Sara Kiani Abari; Behnaz Yazdani; Hadi Farajollahi; Fatemeh Padidari Kalashami; Anahita Zadsar; Hajar Sirous (Research in Pharmaceutical Sciences, 2025)
Background and purpose: One of the most prevalent types of malignancies affecting the cells in the mucosal surface of the oral cavity and pharynx regions is head and neck squamous cell carcinoma (HNSCC). This study analyzed the metabolic profile of genes involved in the metabolism of fatty acids (FAs) to identify biomarkers with prognostic and diagnostic potential in HNSCC. Experimental approach: Gene set enrichment analysis, differential gene expression, and correlation analysis methods were used to examine the enrichment and expression patterns of genes involved in the metabolism of FAs in the HNSCC tissue samples. Gene ontology and network analysis were performed to explore the molecular interactions in the metabolic pathways of FAs. The diagnostic and prognostic potentials of identified highly dysregulated genes in HNSCC were examined by ROC test and Cox-regression methods. Findings/Results: FA-associated metabolic pathways were significantly dysregulated in the HNSC cancer samples. For the diagnosis of HNSC cancer, CYP4B1 and FMO2 could be potential biomarkers, while for the prognosis of HNSCC survival periods, ACOX2, CYP4F12, and ELOVL6 could hold valuable biomarker potential. Conclusion and implications: The findings could help target the metabolism of FAs using the identified biomarkers for the design of new therapeutic opportunities for patients with HNSCC.